2020
DOI: 10.1590/s1677-5538.ibju.2020.0059
|View full text |Cite
|
Sign up to set email alerts
|

How far is too far? Exploring the indications for robotic partial nephrectomy in a highly complex kidney tumor

Abstract: Purpose: The conservative management of localized renal masses has been recently widened to cT2 tumors showing encouraging functional and oncological outcomes (1). This video aims to report the conservative management of a highly complex renal tumor treated with robotic pure enucleation in our center, specifically focusing on preoperative work-up, video-reported surgical steps and perioperative outcomes. Materials and Methods: A 63 year-old lady underwent CT scan revealing a single 75 x 68mm, mainly endophytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Therefore, their potential influence on PSMs remains unexplored in this analysis. Novel technological advancements in robotic surgery and 3D modeling might further enhance surgical precision [29,30] . Thirdly, the unicentric nature of this study could present potential variation in practices and techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their potential influence on PSMs remains unexplored in this analysis. Novel technological advancements in robotic surgery and 3D modeling might further enhance surgical precision [29,30] . Thirdly, the unicentric nature of this study could present potential variation in practices and techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Minervini et al analyzed the use of intraoperative ultrasonography and 3D-virtual models and found that it improved the perception of tumor anatomy and vascularization, maximizing outcomes (14).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this consensus extends to the preferred surgical approach for these masses, with a strong endorsement for enucleative techniques which is the most common reported approach for managing a hilar lesion, adhering closely to the lesion while respecting the limits of the pseudocapsule [21,49]. This strategic choice in surgical method demonstrates an evolved understanding of renal anatomy and pathology, prioritizing organ preservation and functionality alongside effective cancer management [20,90,91].…”
Section: Resection Techniques For Renal Hilar Massesmentioning
confidence: 99%